Science under socialism : East Germany in comparative perspective - Macrakis, Kristie, 1958-2022 1958-2022 (Harvard Univ. Press, 1999)
"The book is organized around general policy issues, institutions, disciplines, and biographies. An international cast of contributors (Americans, former East Germans, and former West Germans) take the reader on a journey from the view of science policymakers, to the construction of "socialist" institutions for science, to the role of espionage in technology transfer, to the social and political context of the chemical industry, engineers, nuclear power, biology, computers, and finally the career trajectories of scientists through the vicissitudes of twentieth-century German history."--BOOK JACKET.